2019
DOI: 10.1002/chem.201904141
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Films of Porous Metal–Organic Polyhedra for Gas Separation

Abstract: Ultrathin films of a robust RhII‐based porous metal–organic polyhedra (MOP) have been obtained. Homogeneous and compact monolayer films (ca. 2.5 nm thick) were first formed at the air–water interface, deposited onto different substrates and characterized using spectroscopic methods, scanning transmission electron microscopy and atomic force microscopy. As a proof of concept, the gas separation performance of MOP‐supported membranes has also been evaluated. Selective MOP ultrathin films (thickness ca. 60 nm) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Inspired by the previous work on the processing of ultrathin films of MOPs using the Langmuir–Blodgett technique, we conduct studies on the structures of hairy MOPs (C 18 -MOP) at the air/water interface . The hairy MOPs (C 12 - and C 18 -MOPs) show similar surface pressure–area compression isotherms (π– A ), suggesting the same structural evolution process during the compression process (Figures S3 and S4 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
“…Inspired by the previous work on the processing of ultrathin films of MOPs using the Langmuir–Blodgett technique, we conduct studies on the structures of hairy MOPs (C 18 -MOP) at the air/water interface . The hairy MOPs (C 12 - and C 18 -MOPs) show similar surface pressure–area compression isotherms (π– A ), suggesting the same structural evolution process during the compression process (Figures S3 and S4 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
“…In a different strategy to the homogeneous dispersion of coordination cages in polymers described above, André s et al 115 reported the deposition of cage-based thin films onto polymer membranes for gas separation. A Rh II 24L24 cuboctahedron functionalised with pendant aliphatic chains, analogous to Rh II 24L24 10 (Figure 2B), assembled at the air-water interface and formed homogenous monolayer films with 2-3 nm thickness through the Langmuir-Blodgett technique.…”
Section: Analogues Of Cu IImentioning
confidence: 99%
“…For this, Langmuir-Schaeffer (LS) or Langmuir Blodgett (LB) techniques were used to form dense monolayers of [Rh 24 (C 12 -bdc) 24 ] (C 12 -bdc = 5-dodecoxybenzene-1,3-dicarboxylate). 37 The hydrophobicity of the aliphatic chains aided the dispersion of the MOCs on the surface of water, leading to the formation of monolayers of ca. 2.5 nm in thickness.…”
Section: Soft Mattermentioning
confidence: 99%